2014
DOI: 10.1021/np400833x
|View full text |Cite
|
Sign up to set email alerts
|

Cladosins A–E, Hybrid Polyketides from a Deep-Sea-Derived Fungus, Cladosporium sphaerospermum

Abstract: Five new fungal hybrid polyketides, cladosins A-D (1-4), that contain a novel linear 6(3)-enamino-8,10-dihydroxy-tetraketide (1 and 2) or 6-enamino-7(8)-en-10-ol (3 and 4) moiety, as well as the biogenetically related cladosin E (5), were isolated from the deep-sea-derived fungus Cladosporium sphaerospermum 2005-01-E3. Their structures (1-5) were elucidated through a combination of spectroscopic data, chemical conversion, and both Mosher's and Marfey's methods for stereochemical assignment. A plausible biogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…In addition, all seaweed derived isolates identified in this study are facultative marine fungi and can be found in marine and terrestrial ecosystems. For instance, C. sphaerospermum [61], C. ramotenellum [62], P. brevicompactum [63], E. nigrum [62], C. rosea [64], and R. oryzae [65] are mainly known from terrestrial environments, but they are also found in deep sea (C. sphaerospermum) [66], Dead Sea water (C. ramotenellum, P. brevicompactum) [67], river sediments (C. rosea) [68], associated with marine sponges (E. nigrum, P. brevicompactum) [69,70], bryozoan Bugula sp. (R. oryzae) [71] or with seagrasses Posidonia oceanica (C. rosea) [72].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all seaweed derived isolates identified in this study are facultative marine fungi and can be found in marine and terrestrial ecosystems. For instance, C. sphaerospermum [61], C. ramotenellum [62], P. brevicompactum [63], E. nigrum [62], C. rosea [64], and R. oryzae [65] are mainly known from terrestrial environments, but they are also found in deep sea (C. sphaerospermum) [66], Dead Sea water (C. ramotenellum, P. brevicompactum) [67], river sediments (C. rosea) [68], associated with marine sponges (E. nigrum, P. brevicompactum) [69,70], bryozoan Bugula sp. (R. oryzae) [71] or with seagrasses Posidonia oceanica (C. rosea) [72].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the 1 H NMR data between the (S)-and (R)-di-MTPA derivatives were calculated as Δδ S−R values. In previous studies, the absolute configuration of acyclic syn 1,3-diols from di-MTPA esters was determined by considering three distinct Δδ values on the left (Δδ L ), center (Δδ C ), and right (Δδ R ) sides of the di-MTPA esters [28,29]. As shown in ▶ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten cladosins (A-D, and F-K) (254-263), a series of C-3-imine-TA analogues, were found in deep-sea-derived C. sphaerospermum. Cladosins 254-257 were discovered from deep-sea-derived C. sphaerospermum 2005-01-E3 cultured with a rice-based medium [199]. Following the OSMAC method, cladosins F-G (258-259) were isolated from the soybean-based medium fermentation of this strain [200].…”
Section: Summary Of Tetramic Acid Products From Marine Microbesmentioning
confidence: 99%